A Comparison of In-Game Brand Placement for Active Versus Passive Players. Issue 2 (2nd July 2016) - Gangadharbatla, Harsha
ABSTRACT: Watching other people play video games is becoming a popular online activity. The current study compares the effectiveness of in-game advertising between two groups of people—active gamers and passive watchers. Hypotheses are proposed using the limited capacity model as a theoretical framework and tested using an experimental method. Results suggest that individuals watching someone else play a video game recall at least four times as many brands as actual players of the video game. However, there are no significant differences in attitudes and purchase intentions due to exposure while playing or watching. Implications are drawn and future directions for research are suggested.